My Pilgrimage in Mission - Whiteman, Darrell L. (International bulletin of mission research, 2023)
Anchored in the Incarnation as a model for cross-cultural ministry, this “pilgrimage” chronicles my life-long effort to connect anthropological insights with mission practice. I note how a linguist, four anthropologists, and an historian—Eugene Nida, Charles Kraft, Alan Tippett, Paul Hiebert, Louis Luzbetak, and Andrew Walls—contributed to my formation as a missiological anthropologist. Two themes that have been the hallmark of my research, teaching, writing, and training are contextualization and incarnational identification. The venues in which my pilgrimage has occurred have been as a mission volunteer in the Congo, a United Methodist missionary in Papua New Guinea and the Solomon Islands, a professor of anthropology in the E. Stanley Jones School of World Mission and Evangelism at Asbury Theological Seminary, a trainer of several thousand missionaries, a member of the American Bible Society Board of Trustees, and various roles in the American Society of Missiology.